Efeito da fragmentação sobre a estrutura de populações de Araucaria angustifolia (Bertol.) Kuntze (Araucariaceae) no sul do Brasil - Müller, Adelcio (2011)
Fragmentation of habitat is the transformation of a continuous natural landscape into habitat patches or fragments, and may result from human settlements, agriculture, resource extraction and/or logging. Besides the influences of habitat loss, populations that remain in these fragments experience conditions similar to those of the surrounding matrix: the process known as "edge influence", one of the determinants which is the type of matrix surrounding the fragment. In the Southern region of Brazil is found the Mixed Ombrophylous Forest, also known as Araucaria Forest, and the species Araucaria angustifolia remains threatened by the use of its wood for domestic and commercial settings, as well conversion of its natural habitat into agropastoral activities and plantations of exotic species. The size distribution of the population carries a wealth of demographic information and often is the most unequivocal attribute available and accessible to a population. Therefore, the aim of this study was to obtain information on the population ecology of Araucaria angustifolia (Bertol.)O. Kuntze (Araucariaceae) on edges facing urban matrix, pasture matrix and agricultural matrix. In each of the five fragments were established 50 plots of 10m x 20m parallel to edge, with 25 deployed immediately at the edge and 25 at a distance of 120 meters from the edge. Within these plots, all individuals of Araucaria angustifolia were evaluated. There was no effect of edge on the structure of populations of Araucaria angustifolia evaluated for most variables, however; however, when we evaluated together matrix and shape of the fragments, we found a direct relationship with the density of individuals. The hypothesis that the population structure of Araucaria differs between the edge and inside regardless of shape, size or type of matrix has not been comproved, possibly because of the large variation in the population parameter between the fragments, independently of shape and matrix. But when these two characteristics were assessed together, they were significantly correlated with the total density of each fragment and its edge and interior.